Understanding nicotine and tobacco addiction - Symposium on Understanding Nicotine and Tobacco Addiction (2005 : Novartis Foundation); Bock, Gregory; Goode, Jamie; Wiley InterScience (Online service) (Chichester, UK ; Hoboken, NJ : John Wiley & Sons, 2006)
Covers the basic issues concerning the nature of the worldwide health problem posed by cigarette smoking. Exploring the psychoydnamics of cigarette addiction, this book reviews the pharmacology and biochemistry of nicotine and its effect on the brain. Italso covers various approaches to therapy, and discusses how best to treat nicotine addiction.
The hazards of smoking and the benefits of stopping / Richard Peto, Richard Doll -- Animal models for nicotine dependence / Ian Stolerman -- Defining and assessing nicotine dependence in humans / Robert West -- Nicotinic acetylcholine receptor functions in the CNS investigated with a novel method of stereotaxic gene re-expression in knockout mice / Uwe Maskos, Sylvie Granon, Philippe Faure, Jean-Pierre Changeux -- Nicotine-mediated activation of signal transduction pathways / Marina R. Picciotto -- Complementary roles for the accumbal shell and core in nicotine dependence / David Balfour -- The dopamine D3 system : new opportunities for dopamine-based reward / Christian Heidbreder -- Pathways and systems involved in nicotine dependence / Athina Markou -- Localizing tobacco dependence pathways with functional brain imaging / Arthur L. Brody -- Pharmacogenetic approaches to nicotine dependence treatment / Caryn Lerman -- Pharmacogenomics and smoking cessation / Robert Walton -- What limits the efficacy of current nicotine replacement therapies? / Peter Hajek -- Exploring behavioural mechanisms of nicotine replacement therapy for smoking cessation / Saul Shiffman, Stuart Ferguson, Deborah Scharf -- Modifying the metabolism of nicotine as a therapeutic strategy / Rachel F. Tyndale, Edward M. Sellers -- Challenges in discovery and development of pharmacotherapies for tobacco addiction / William A. Corrigall.
Symposium held at the Novartis Foundation, London, 17-19 May 2005.
Includes bibliographical references and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Nicotine addiction -- Congresses; Tobacco use -- Physiological aspects -- Congresses; Tobacco use -- Psychological aspects -- Congresses; Smoking Cessation -- Congresses; Tobacco Use Disorder; Nicotine -- pharmacokinetics; Nicotine -- pharmacology; Tabagisme; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); Congresses; Electronic books